2008
DOI: 10.1021/jf8017063
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidative Activity and Antidiscoloration Efficacy of Ergothioneine in Mushroom (Flammulina velutipes) Extract Added to Beef and Fish Meats

Abstract: The antioxidative property of a hydrophilic extract prepared from the fruiting body of edible mushroom ( Flammulina velutipes) was evaluated. The mushroom extract contained ergothioneine (ERT) at a level of 3.03 +/- 0.07 mg/mL, showed higher 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging activity, and suppressed lipid oxidation of bigeye tuna meat more effectively than authentic L-ERT added at the same concentration. The authentic L-ERT had stronger total reducing power than the mushroom extract and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
81
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 91 publications
(90 citation statements)
references
References 28 publications
6
81
0
3
Order By: Relevance
“…The extract from edible mushroom, Flammulina velutipes, has been reported to be a promising source of natural antioxidants and melanosis-inhibiting agents (Jang, Sanada, Ushio, Tanaka, & Ohshima, 2002. It contains a significant amount of 2-thioll-histidine-betaine (ergothioneine, ESH) (Bao, Ushio, & Ohshima, 2008. Although thiol-containing compounds, such as ESH, are known to inhibit PO activity, no studies have assessed the effect of such compounds on the gene expression of proPO, a precursor of PO that plays an important role in melanosis formation in live crustaceans.…”
Section: Introductionmentioning
confidence: 99%
“…The extract from edible mushroom, Flammulina velutipes, has been reported to be a promising source of natural antioxidants and melanosis-inhibiting agents (Jang, Sanada, Ushio, Tanaka, & Ohshima, 2002. It contains a significant amount of 2-thioll-histidine-betaine (ergothioneine, ESH) (Bao, Ushio, & Ohshima, 2008. Although thiol-containing compounds, such as ESH, are known to inhibit PO activity, no studies have assessed the effect of such compounds on the gene expression of proPO, a precursor of PO that plays an important role in melanosis formation in live crustaceans.…”
Section: Introductionmentioning
confidence: 99%
“…DPPH scavenging rate of 65.85% and hydroxyl radical scavenging rate of 71.24% were obtained at 200 μg/mL of FvP-3. Previous studies reported that mushroom extracts had free radical scavenging and antioxidative activities not only in vitro but also in vivo (Bao et al, 2008;Cheung and Cheung, 2005;Jang et al, 2004;Puttaraju et al, 2006). Alcoholic and aqueous extracts of F. velutipes have been evaluated for antioxidant activity by lipoxygenase inhibition, DPPH assay and deoxyribose assays (Bao et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…ERGO exerts its antioxidant activity at sub-mM to mM concentrations [34][35][36], whereas the hepatic ERGO concentration in control and DMN-treated mice was at most 100~200 µM (Fig. 3D).…”
Section: Discussionmentioning
confidence: 98%